Catholic Scout Association of Portugal: motivations of adult volunteers - SARDINHA, BOGUSLAWA MARIA BARSZCZAK (2012)
When somebody starts analyzing the volunteering phenomenon, the question of why do people volunteer immediately arises. What reasons make people give away their time for helping others? What motivates volunteers? Volunteering is a great way to become involved in the community. Through volunteering an individual becomes part of the solution. He is able to demonstrate community commitment, to gain community contacts and to support many social causes. The World Organization of the Scout Movement and its National Scout Associations play a very important role by contributing to the education of young people in order to help them have a constructive role in society. The Portuguese Catholic Scout Association (CNE) counts more than 71.000 members in c.1100 local groups, including c.13.000 adult volunteers, which makes CNE the largest youth association in the country. Almost all the work in the Portuguese Catholic Scout Association is done by permanent volunteers, many of them giving more than 200 volunteer hours per year. The most important work consists in education and tutoring of young girls and boys from 6 to 22 years old.The motivation for volunteering for so many hours is a very interesting study. It is also critical for CNE leaders to understand how to motivate volunteers to join and to retain those adult volunteers. The objective of this work is to try to understand the motivation of the adults who volunteer in the Portuguese Catholic Scout Association. This organization, as many others, is facing the problem of insufficient number of volunteers, comparing with the increasing necessity of intervention. In this work we present the findings of the research developed in the Portuguese Catholic Scout Association about the volunteering involvement in this organization, especially the motivation of adults. This is a unique study about volunteering motivations developed in Portugal based on empiric data of one of the most important e and influent youth organization.